Cerebral changes occurring in arginase and dimethylarginine dimethylaminohydrolase (DDAH) in a rat model of sleeping sickness. - Donia Amrouni (Public Library of Science (PLoS), 2011)
Background Involvement of nitric oxide (NO) in the pathophysiology of human African trypanosomiasis (HAT) was analyzed in a HAT animal model (rat infected with Trypanosoma brucei brucei). With this model, it was previously reported that trypanosomes were capable of limiting trypanocidal properties carried by NO by decreasing its blood concentration. It was also observed that brain NO concentration, contrary to blood, increases throughout the infection process. The present approach analyses the brain impairments occurring in the regulations exerted by arginase and N(G), N(G)-dimethylarginine dimethylaminohydrolase (DDAH) on NO Synthases (NOS). In this respect: (i) cerebral enzymatic activities, mRNA and protein expression of arginase and DDAH were determined; (ii) immunohistochemical distribution and morphometric parameters of cells expressing DDAH-1 and DDAH-2 isoforms were examined within the diencephalon; (iii) amino acid profiles relating to NOS/arginase/DDAH pathways were established. Methodology/principal findings Arginase and DDAH activities together with mRNA (RT-PCR) and protein (western-blot) expressions were determined in diencephalic brain structures of healthy or infected rats at various days post-infection (D5, D10, D16, D22). While arginase activity remained constant, that of DDAH increased at D10 (+65%) and D16 (+51%) in agreement with western-blot and amino acids data (liquid chromatography tandem-mass spectrometry). Only DDAH-2 isoform appeared to be up-regulated at the transcriptional level throughout the infection process. Immunohistochemical staining further revealed that DDAH-1 and DDAH-2 are contained within interneurons and neurons, respectively. Conclusion/significance In the brain of infected animals, the lack of change observed in arginase activity indicates that polyamine production is not enhanced. Increases in DDAH-2 isoform may contribute to the overproduction of NO. These changes are at variance with those reported in the periphery. As a whole, the above processes may ensure additive protection against trypanosome entry into the brain, i.e., maintenance of NO trypanocidal pressure and limitation of polyamine production, necessary for trypanosome growth.